029 Botulinum toxin injections into the urethral sphincter for managing urinary retention in Fowler's syndrome. Issue 9 (12th August 2022) - Ananthavarathan, Piriyankan; Malladi, Prasad; Pakzad, Mahreen; Simeoni, Sara; Panicker, Jalesh
Abstract : Background: Fowler's Syndrome typically presents as chronic urinary retention in young women, charac- terised by poor urethral sphincter relaxation. Standard treatment sacral neuromodulation is invasive and may not necessarily be appropriate for all patients. Aims: To evaluate efficacy and safety of botulinum toxin injections into the urethral sphincter in women with Fowler's syndrome Results: 17 women (mean age 36.9±12.4 years) diagnosed with Fowler's Syndrome (abnormal urethral sphincter EMG and/or elevated urethral pressure profile) unsuitable for sacral neuromodulation received 100U botulinum toxin injected EMG-guided into the external urethral sphincter between 2020-21. 48 injec- tions were administered: 9 patients received >1 injection (median 4 injections/patient, median interval 3.50 months). 12 women (71%) reported improvements following 37 injections (77%): 62% reported reduced need for self-catheterisation, 32% became catheter-free, and 8% reported improved urinary flow. Mean IPSS score (n=6) improved from 20.5 to 12.83, while Patient Perception of Intensity of Urgency score significantly improved from 0.87 to 2.03 (p<0.05). Only mild side effects were reported: transient stress incontinence (n=3), short-lasting pain and bleeding (n=3), increased urgency incontinence (n=2). Conclusion: Minimally-invasive urethral sphincter botulinum toxin injections significantly improve urinary symptoms among women with Fowler's syndrome and is well tolerated.